Challenges in Program Evaluation of Health Interventions in Developing Countries - Wynn, Barbara O. (RAND Corporation, 2005)
Health interventions that are effective in developed countries may not be as effective in developing countries given the differing social, economic, cultural, and infrastructure factors that may affect a program's implementation and outcomes. This monograph is intended to promote an understanding of why program evaluation is a critical component of any health intervention and to stimulate discussion on ways to make evaluation of health interventions in developing countries more rigorous.